2020
DOI: 10.3390/ijerph17155347
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Earthquake Experience on Disaster Education for Children and Teens

Abstract: The purpose of this study is to examine the factors of disaster experience that impact the effectiveness of disaster education on school students (children and teens). Following the magnitude 5.4 Pohang earthquake in 2017, Pohang City Hall conducted a school earthquake disaster education program over a period of four months (August to November) in 2018. Professors and graduate students from the Ulsan National Institute of Science and Technology taught around 5000 middle and high school students, while also con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…In addition, it was concluded that there is not a standard in the educational system of Ecuador to prepare students for tsunamis. 61 Yeon et al (2020) 81 South Korea Quantitative/ correlationalobservational study Total 3316 middle-school and high-school students It was indicated that disaster education after Pohang earthquake was effective because students were motivated to learn protective actions.…”
Section: Description Of Outcomesmentioning
confidence: 99%
“…In addition, it was concluded that there is not a standard in the educational system of Ecuador to prepare students for tsunamis. 61 Yeon et al (2020) 81 South Korea Quantitative/ correlationalobservational study Total 3316 middle-school and high-school students It was indicated that disaster education after Pohang earthquake was effective because students were motivated to learn protective actions.…”
Section: Description Of Outcomesmentioning
confidence: 99%
“…Disaster education should be taught to students at all levels of education [1] using diving tools and technology [2]. Various kinds of devices in residential areas can be used to learn about disasters, e.g., water, fire, rope, wet sacks, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Students can become the "agents of change" in transforming and improving the understanding and preparedness of disaster education. They can share and discuss with their families what they have learned at school about disaster preparedness [1]. Furthermore, disaster education can be delivered in various forms of education by local policies [5], including lessons, training, discussions with teachers and friends, reading and listening, using hypermedia systems, games, after-class activities, and intercultural projects online that can help increase survival and trauma healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of Iran's population today consists of children and teenagers, who form one of the most important groups subjected to disasters and accidents (Mehr Aeen & Kazemi, 2016). Earthquakes can also change the attitude of students toward school and education, particularly when they are kept away from school for a very long time (Yeon, Chung, Im, 2020). They also cause physical and mental harm and cut off educational services (Baytiyeh, 2017;Trip, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%